The future of clinical engineering the challenge of change. - Grimes, S.L (IEEE Engineering in medicine and biology magazine)
Clinical engineering is at a strategic inflection point. Technical, economic, regulatory, and cultural dynamics are at work shaping the future of healthcare delivery. As the nature of healthcare delivery is transformed by these forces, the types and mix of technology management and support services needed by the industry are changing significantly. Clinical engineering has a relatively short opportunity to adopt a service model that will meet these changing needs. Delay or failure to adopt an effective service model as we pass through the inflection point will result in a diminished role for clinical engineering in healthcare technology management as other technical professionals move in to fill the need. The question is: will clinical engineering rise to the challenge?.